(untitled) - Procházka, Karel Jan (Aura musica, 2020)
It is useful to appropriately complements listening education based on world fundamental music composition even with the pieces of Czech music from the given periods. Regarding music periods such as the 17th century (Michna) and 19th century (Smetana, Dvořák etc.) there are no difficulties. However, the difficulty comes with the 18th century. There is quite a large amount of information and recordings related to Zelenka, Mysliveček and Brixi; nevertheless, this presentation tries to publicize the home music production, especially by so called schoolmaster's music, which is of a very high level even though mostly discarded in archives. Basic data concerning various authors and their revived recordings will be presented here (Habermann, Loos, Mensi, Brixi, Ryba, etc.).
Keywords: listening education; Czech music; publicizing home music production; schoolmaster's music; archives; revived music